Analysis of novel multi-input KY boost converter. (2022) - Pushpavalli, M.; Jothi Swaroopan, N.M.; Sivagami, P.; Abirami, P.; Kavitha, M.; Geetha, V.
Abstract: The KY converter gets its name from a paper titled "KY converter and its derivatives" by the author K.I. Hwu and Y.T. Yau (KY converter). The literature survey of various KY converters analysed from 2007 to 2017. From the research study, it is apparent that KY converters have so many advantages than conventional converters. This KY boost converters are mainly used for boosting the voltage from lower value to higher value. This converter also possesses the advantages of low ripples, high Power applications and stable converter. By analysing the performance, the most suitable KY boost converter is developed by Hwu, K.I. This KY boost converter single-stage converter. The same converter is taken for the multi-input analysis. This paper analysis about Multi-Input (MI) converter systems rather than individual converters. The individual converter results in a large volume of the device in the system and high expenditure. The other multi-input converters have at least one zero in the right hand of the jw plane, which leads to instability in the converters. This multi-input KY boost converter transfer function proves that all the poles and zeros are present in the left hand of the jw plane. So, the stability of the converter is good. Multi-input Converters in which Multi-input KY boost converter is superior to other converters.